Water stress limits transpiration and growth of European larch up to the lower subalpine belt in an inner‐alpine dry valley. Issue 2 (20th July 2018) - Obojes, Nikolaus; Meurer, Armin; Newesely, Christian; Tasser, Erich; Oberhuber, Walter; Mayr, Stefan; Tappeiner, Ulrike
Summary: Climate change will further constrain water availability in dry inner‐alpine environments and affect water relations and growth conditions in mountain forests, including the widespread larch forests. To estimate the effects of climate conditions on water balance and growth, variation in sap flow and stem radius of European larch was measured for 3 yr along an elevation transect from 1070 to 2250 m above sea level (asl) in an inner‐alpine dry valley in South Tyrol/Italy. Additionally, long‐term climate–growth relations were derived from tree cores. Sap flow and radial growth were reduced in dry periods up to an elevation of 1715 m, leading to maximum annual growth at 2000 m. In a wet year no growth difference between elevations was observed. Long‐term tree ring data showed a positive growth response to precipitation up to 1715 m and to temperature only above 2000 m. Our results demonstrate that reduced water availability and higher atmospheric water demand limit larch at low elevation within dry Alpine regions. This indicates a general upward shift of this species' elevational amplitude upon climate change, and respective negative effects on future silvicultural use and ecosystem services at lower elevations in the European Alps.